Evaluation of the Futsal Development Program at SMP Negeri 10 Medan in 2023 - Dalimunthe, Syamsinur; Keliat, Pedomanta (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2025)
This study aims to evaluate the context, input, process, and product (CIPP) components of the futsal development program at SMP Negeri 10 Medan. Employing a descriptive qualitative approach, the research involved 25 participants, including coaches, players, and futsal observers. Data were collected using observation sheets and interviews. The findings reveal that: (1) the context evaluation, covering the background and planning of the development program, was rated fairly good with a score of 57; (2) the input evaluation, including information dissemination, facilities and infrastructure, government and community support, and human resources, was fairly good with a score of 104; (3) the process evaluation, concerning program implementation, coordination, selection of athletes and coaches, and facility feasibility, was fairly good with a score of 180; and (4) the product evaluation, focusing on achievements, was fairly good with a score of 20. The study concludes that the futsal program at SMP Negeri 10 Medan is generally adequate but still requires improvement in terms of player quality, budget allocation, structured coaching programs, and institutional support to enhance performance in interschool competitions.